New Species of Macroalgae from Tamengo Formation, Ediacaran, Brazil - Diniz, Cleber Q. C.; Leme, Juliana de Moraes; Boggiani, Paulo C. (Frontiers in Earth Science, 2021)
The Tamengo Formation (Corumbá Group) is an important Ediacaran stratigraphic unit in South America due to the presence of metazoan fossils and geochemistry data of carbonate rocks, with excellent geochronological delimitation (between 555–541 Ma) obtained by U–Pb dating on volcanic zircons. The present work shows three new species of macroalgae found as carbonaceous compressions and studied for their morphology and taxonomy. All new taxa are characterized as centric macroalgae; Tamengophyton espinosa sp. nov. is a fan-shaped alga with striated thalli, dichotomous branches, trichomes with perpendicular growth, and a connecting membrane. Ladariella hidria sp. nov. is formed by a set of striated and branched thalli in a cylindrical form with almond-shaped structures in the top. Ladariophyton veinosa sp. nov. is characterized by the main growth thallus and an enlarged longitudinal structure at the center. These new occurrences of macroalgae add to the largest life assemblages in the Neoproterozoic of South America, which contributes to documentation of the evolutionary history of macroalgae and the paleoecological settings of the Late Ediacaran.